Effectiveness of Trade Business Licensing Services Through The Papa Joss Program In The Padang Pariaman Regency - Arib Zhafran Amzan; Afif Syarifudin Yahya (Journal of Economics, Business, and Government Challenges, 2022)
Effectiveness of Trade Business Licensing Services Through The Papa Joss Program In The Padang Pariaman Regency